Historical evidence that identifies the Río de la Plata poet Esteban de Luca as the probable author of the stanza “Long time the oppressed Peruvian” - González Bolaños, Jorge Federico (2024)
The Río de la Plata poet Esteban de Luca is the probable author of the stanza “Long time the oppressed Peruvian”. This stanza belongs to the “First patriotic song” of 1821 collected as the first document in The album of Ayacucho. The “First patriotic song” reaffirms the political proposal of General Manuel Belgrano raised in the Congress of Tucumán, in a secret session on July 6, 1816, to restore the legitimate government of the Incas in the United Provinces of South America. The “First patriotic song” was specially inspired by the Argentine National Anthem, the work of another famous Río de la Plata poet called Vicente López y Planes, friend of Esteban de Luca.